Morphology and roughness in the hydraulics of large bed element channels - Zgheib, Philippe W. (1996)
The evolution of natural steep channels is a function of two factors in accordance with the principle of least action: flow distribution in the channel and terrain geomorphology. Large bed elements (LBE) occurring in the stream bed act on both factors. Stream flow in steep natural terrain occurs in two basic regimes: hydraulic and morphological. The suggested hypotheses define the LBE roughness ratio of substrate size to flow depth. In the morphological regime maximum flow forms the stream channel. Statistical regression analyses on field data correlate flow distribution, roughness ratio and channel slope. The relevance of this correlation can be verified in different flow regimes and geographical regions.